Simulation of nitrogen balance in rice-wheat systems of the Indo-Gangetic plains - Pathak, H.; Li, C.; Wassmann, R.; Ladha, J.K. (Wiley, 2006)
Crop growth simulation models provide a means to quantify the effects of climate, soil, and management on crop growth and biogeochemical processes in soil. The Denitrification and Decomposition (DNDC) model was evaluated for its ability to simulate N dynamics and balance in the rice (Oryza sativa L.)–wheat (Triticum aestivum L.) cropping systems in the Indo‐Gangetic Plains with various N and water management practices. The observed crop yield, N uptake, and losses of N were in good agreement with the values predicted by the model. In the rice–wheat systems, current annual inputs of N through fertilizer, manure, biological fixation, atmospheric deposition, and irrigation were 98, 37, 17, 8, and 7 kg N ha−1, respectively, while outputs through uptake, volatilization, leaching, and denitrification were 175, 14, 12, and 4 kg N ha−1, respectively. The northwestern transects of the Indo‐Gangetic Plains (Punjab and Haryana) showed greater yields and N uptake because of a higher amount of N use and more favorable climatic conditions than those in the eastern transects (Uttar Pradesh, Bihar, and West Bengal). Volatilization was the dominant N loss mechanism in Punjab and West Bengal while NO3 leaching was dominant in Bihar, Uttar Pradesh, and West Bengal. The simulated balance of N was negative in all the states. The largest depletion of soil N was estimated in Bihar, followed by Uttar Pradesh, Haryana, Punjab, and West Bengal. The study suggests that better N management is required to arrest the depletion of soil N.